Desain Pabrik Pengolahan Kopra Berbasis Arsitektur Industri Modern yang Berkelanjutan dan Potensi Lokal di Kabupaten Konawe Selatan - Muhamad Resky; Abd. Azis Alimuddin; Andas Budy (Universitas Medan Area, 2026)
Indonesia, as an agrarian country, has significant potential in the agricultural sector, including coconut plantations which are among the leading commodities in Southeast Sulawesi. Konawe Selatan Regency is recognized as one of the largest coconut-producing areas; however, the predominance of traditional processing methods has resulted in low added value and limited competitiveness of its products. This issue forms the basis for the planning and design of a Copra Processing Industry in Konawe Selatan Regency. Through a case study method and comparative analysis, this research evaluates various design parameters focusing on the application of modern industrial concepts that are functional, efficient, and environmentally friendly, while also considering local potential and community welfare. The design approach involves site massing arrangements, effective circulation systems, the application of structures and materials suited to production needs, and the integration of public spaces that support social interaction and community education. Thus, the copra processing industry serves not only as a production center but also as a means of economic empowerment, cultural preservation, and sustainable regional development. The findings provide valuable insights for architects, engineers, and policymakers in designing industrial facilities that implement modern, functional, efficient, sustainable, and environmentally friendly concepts, while simultaneously contributing to the development of local potential and the improvement of community welfare.